A Review on Importance of Pharmacovigilance (International Journal of Scientific Research in Science and Technology, 2024)
In the labyrinth of healthcare, Pharmacovigilance (PV) serves as the beacon of safety, navigating through the intricate web of drug interactions and effects on human health. As pharmaceutical and biotechnological marvels strive to diagnose, prevent, or cure diseases, the significance of PV cannot be overstated, especially in a country as populous as India, where over a billion individuals stand as potential recipients of medicinal interventions. Despite India’s involvement in the Uppsala Monitoring Center (UMC) program, its contribution to the global PV database remains modest, underscoring the need for a more robust and participatory approach. Signal assessment, utilizing tools such as the World Health Organization (WHO) scale and the Naranjo scale, emerges as a crucial yet intricate process in discerning causality amidst the complex tapestry of drug effects.This article embarks on a systematic exploration of PV in India, tracing its journey from inception to the contemporary landscape. It delves into various strategies and propositions aimed at fortifying the PV framework and enhancing the culture of adverse drug reaction (ADR) reporting nationwide.In the realm of PV, the paramount concern lies in the under-reporting of ADRs, a challenge exacerbated by the escalating instances of patient hospitalization due to adverse drug effects. Unraveling the intricacies of causation becomes a formidable task, particularly in scenarios where patients are subjected to a confluence of multiple medications simultaneously. This review ventures into the diverse arsenal of assessment scales employed in ADR evaluation, each offering a unique vantage point in the quest to identify causative agents. From the intricate dance of pharmacokinetics to the subtle nuances of drug interactions, every facet of PV is scrutinized with meticulous attention, echoing the imperative of safeguarding patient well-being in every therapeutic endeavor. As India treads the path of PV, it stands at the threshold of discovery and innovation, poised to unravel the mysteries of drug safety with diligence and resolve. With each stride forward, the nation inches closer to a future where the promise of pharmaceutical advancements is matched only by the assurance of patient safety.